Promoting employee flourishing and performance: the roles of perceived leader emotional intelligence, positive team emotional climate, and employee emotional intelligence - A'yuninnisa, Rizqi N.; Carminati, Lara; Wilderom, Celeste P. M. (Frontiers in Organizational Psychology, 2024)
Through the lens of the of Emotion as Social Information (EASI) model, we examined the influence of perceived leader emotional intelligence on employee job flourishing and performance, produced via employee emotional intelligence, under the condition of positive team emotional climate. We collected data with a two-wave survey design involving 1,210 primary school teachers and their 169 leaders. The hypothesized model was then tested using a multilevel structural equation model in Mplus. As hypothesized, the results suggest that perceived leader emotional intelligence positively affects the emotional intelligence level of followers, which enhances their job flourishing and performance. Reflecting the emotional display rules within the team, positive team emotional climate moderates this effect from leader to followers, in such a way that the relationship between perceived leader emotional intelligence and employee emotional intelligence is stronger when this positive team emotional climate is high rather than low. Our findings shed light on the affective impact of leaders and their teams as relevant sources of socio-emotional information for employees at work. Limitations of the present study and directions for future studies are included in the paper.